2004
DOI: 10.2214/ajr.183.3.1830671
|View full text |Cite
|
Sign up to set email alerts
|

MRI for Clinically Suspected Appendicitis During Pregnancy

Abstract: Our results suggest that MRI is helpful in the examination and diagnosis of acute appendicitis in pregnant patients. MRI may therefore be a good alternative to CT in pregnant patients for whom sonographic findings are nondiagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 9 publications
3
55
0
Order By: Relevance
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 80%
“…Technological developments have made ultrafast sequences possible, resulting in shorter examination times and fewer motion artifacts. Detection of appendicitis with MRI has been published in a small group of pregnant and non-pregnant patients [13][14][15][16][17][18][19]. This is, to our knowledge, the first prospective blinded clinical study, in more than 100 patients, to evaluate MRI in patients clinically suspected of having appendicitis.…”
Section: Introductionmentioning
confidence: 97%
“…28 Several studies have reported non-visualization of the appendix in a large percentage of pregnant women with suspected appendicitis. [29][30][31][32][33] However, in a review of studies on the value of ultrasound diagnostics during appendicitis in pregnancy, sensitivity ranged from 67 to 100% and specificity of 83 to 96%, compared with the general population, in which sensitivity and specificity were 86 and 96%, respectively. 34 Several factors influence the performance of ultrasound diagnosis of appendicitis in pregnancy, including gestational age, body mass index (BMI), and most importantly, the training and experience of the examiner.…”
Section: 28mentioning
confidence: 99%
“…Both CT and ultrasound plays important roles in acute appendicitis diagnosis. CT is found to be more accurate thus was the preferred imaging modality [10] [11].…”
Section: Discussionmentioning
confidence: 99%